Catalytic Interactions and Molecular Docking of Bile Salt Hydrolase (BSH) from L. plantarum RYPR1 and Its Prebiotic Utilization - Yadav, Ruby; Singh, Puneet K.; Puniya, Anil K.; Shukla, Pratyoosh (Frontiers in Microbiology, 2017)
Prebiotics are the non digestible carbohydrate, which passes through the small intestine into unmetabolized form, reaches the large intestine and undergoes fermentation by the colonic bacteria thus; prebiotics stimulate the growth of probiotic bacteria. Further, bile salt hydrolase (BSH) is an enzyme that catalyses the deconjugation of bile salt, so it has enormous potential towards utilizing such capability of Lactobacillus plantarum RYPR1 towards detoxifying through BSH enzyme activity. In the present study, six isolates of Lactobacillus were evaluated for the co-aggregation assay and the isolate Lactobacillus plantarum RYPR1 was further selected for studies of prebiotic utilization, catalytic interactions and molecular docking. The prebiotic utilization ability was assessed by using commercially available prebiotics lactulose, inulin, xylitol, raffinose and oligofructose P95. The results obtained revealed that RYPR1 is able to utilize these probiotics, maximum with lactulose by showing an increase in viable cell count (7.33 + 0.02 to 8.18 + 0.08). In addition, the molecular docking of bile salt hydrolase (BSH) from Lactobacillus plantarum RYPR1 was performed which revealed the binding energy -4.42 KJ/mol and 7.03 KJ/mol . This proves a considerably good interactions among BSH and its substrates like taurocholic acid (-4.42 KJ/mol) and glycocholic acid (-7.03 KJ/mol). These results from this study establishes that Lactobacillus plantarum RYPR1 possesses good probiotic effects so it could be used for such applications. Further, molecular dynamics simulations were used to analyze the dynamic stability of the of modeled protein to stabilize it for further protein ligand docking and it was observed that residues Asn12, Ile8 and Leu6 were interacting among BSH and its substrates i.e. taurocholic acid and Lys88 and Asp126 were interacting with glycocholic acid. These residues were interacting when the docking was carried out with stabilized BSH protein structure, thus, these residues may have a vital role in stabilizing the binding of the ligands with the protein.